Quantum dot bio-conjugate: as a western blot probe for highly sensitive detection of cellular proteins - Kale, Sonia; Kale, Anup; Gholap, Haribhau; Rana, Abhimanyu; Desai, Rama; Banpurkar, Arun G.; Ogale, Satishchandra; Shastry, Padma (Journal of Nanoparticle Research, 2012)
In the present study, we report a quantum dot (QD)-tailored western blot analysis for a sensitive, rapid and flexible detection of the nuclear and cytoplasmic proteins. Highly luminescent CdTe and (CdTe) ZnS QDs are synthesized by aqueous method. High resolution transmission electron microscopy, Raman spectroscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray diffraction are used to characterize the properties of the quantum dots. The QDs are functionalized with antibodies of prostate apoptosis response-4 (Par-4), poly(ADP-ribose) polymerases and beta actin to specifically bind with the proteins localized in the nucleus and cytoplasm of the cells, respectively. The QD-conjugated antibodies are used to overcome the limitations of conventional western blot technique. The sensitivity and rapidity of protein detection in QD-based approach is very high, with detection limits up to 10 pg of protein. In addition, these labels provide the capability of enhanced identification and localization of marker proteins in intact cells by confocal laser scanning microscopy.
Keywords: Detection; Imaging; nanomedicine; quantum dot; Rapid; sensors; Western blot

Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting

Thiol and halometallate, mutually passivated quantum dot ink for photovoltaic application - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2019)
Tunable-band-gap colloidal QDs are a potential building block to harvest the wide-energy solar spectrum. The solution-phase surface passivation with lead halide-based halometallate ligands has remarkably simplified the processing of quantum dots (QDs) and enabled the proficient use of materials for the development of solar cells. It is, however, shown that the hallometalate ligand passivated QD ink allows the formation of thick crystalline shell layer, which limits the carrier transport of the QD solids. Organic thiols have long been used to develop QD solar cells using the solid-state ligand exchange approach. However, their use is limited in solution-phase passivation due to poor dispersity of thiol-treated QDs in common solvents. In this report, a joint passivation strategy using thiol and halometallate ligand is developed to prepare the QD ink. The mutually passivated QDs show a 50% reduction in shell thickness, reduced trap density, and improved monodispersity in their solid films. These improvements lead to a 4 times increase in carrier mobility and doubling of the diffusion length, which enable the carrier extraction from a much thicker absorbing layer. The photovoltaic devices show a high efficiency of 10.3% and reduced hysteresis effect. The improvement in surface passivation leads to reduced oxygen doping and improved ambient stability of the solar cells.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Reduction of trap and polydispersity in mutually passivated quantum dot solar cells - Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (ACS Applied Energy Materials, 2020)
Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport process. However, the ligand exchange process often resulted in reduced surface passivation, inhomogeneous QD fusion, and deterioration of energy band gap, which adversely impact their performance in solar cells. Here, we introduce a surface passivation strategy where the QDs are mutually passivated by the organic ligand 3-methyl mercapto propionate and inorganic halometallate ligands to develop a conducting QD ink. The mutually passivated QDs (MPQDs) show significant improvement in optoelectronic properties in maintaining the trap-free energy band gap and size monodispersity. The photovoltaic performance of MPQDs shows a 33% average increase in power conversion efficiency (PCE) over the conventional halometallate passivation to attain 9.6% PCE in MPQD solar cells. The improvements in photovoltaic parameters are corroborated by the reduction in density of the intermediate trap states and an increase in depletion width and diffusion length in MPQD-based solar cells.
Keywords: polydispersity; quantum dot; solar cells; surface passivation; trap states

Solution-phase hybrid passivation for efficient infrared-band gap quantum dot solar cells - Mahajan, Chandan; Sharma, Ashish; Rath, Arup K. (ACS Applied Materials & Interfaces, 2020)
The broad tunability of the energy band gap through size control makes colloidal quantum dots (QDs) promising for the development of photovoltaic devices. Large-size lead sulfide (PbS) QDs, exhibiting a narrow energy band gap, are particularly interesting as they can be used to augment perovskite and c-Si solar cells due to their complementary NIR absorption. However, their complex surface chemistry makes them difficult to process for the development of solar cells. The shape of the QDs transformed from octahedron to cuboctahedron as their size increases, a phenomenon guided by surface energy minimization. As a result, the surface properties change drastically for large-size QDs, which exhibit nonpolar (200) facets and polar (111) facets, as opposed to only (111) facets in small-size QDs. Recent advancements in solution-phase surface passivation strategies, used for the development of high-performance solar cells using the small size and wide band gap QDs, failed to translate a similar enhancement in the case of large-size and narrow band gap QDs. Here, we report a hybrid passivation strategy for large-size and narrow band gap QDs to passivate both (111) and (200) facets, respectively, using inorganic lead triiodide (PbI3-) and organic 3-chloro-1-propanethiol (CPT). By employing charge balance calculation, we identified the desired narrow band gap for QDs to complement the perovskite and c-Si absorption. The distinct choice of the organic ligand CPT enhances the colloidal stability of QDs in the solution phase and improves surface passivation to stop QD fusion in solid films. Photophysical properties show narrower excitonic and emission peaks and a reduction in the Stokes shift. Hybrid passivation leads to a 94% increase in the power conversion efficiency of solar cells and a 74% increase in the external quantum efficiency at the excitonic peak.
Keywords: infrared band gap; polydispersity; quantum dot; solar cells; surface passivation; trap states

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation